Pernikahan Ideal Menurut Najīb al-Kailānī dalam Novel Lail wa Qudbhan (Analisis Semiotika Roland Barthes) - Rahimal Khair (Jurusan Bahasa dan Sastra Arab Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2020)
Marriage is a husband and wife bond between men and women that is considered sacred by Muslims. This study aims to reveal how the ideal marriage in the view of Najīb al-Kailānī in a novel entitled Lail wa Qudhban with the help of Roland Barthes's semiotics theory. The research method used is a qualitative method. Data collection techniques used were documentation and data analysis techniques used were analytical descriptions. The results of the study showed that Najīb al-Kailānī in the novel Lail wa Qudbhan gave four criticisms and messages about an ideal marriage. Namely: a), marriage is not only husband and wife ties that are considered sacred but husband and wife ties aiming to meet each other's physical and spiritual needs and expecting the presence of a baby(s) or child, b), marriage should be based on sincere love, c), marriage not intended to be looked charming but still giving freedom, d), marriage is built on some considerations according to religious teachings, not because of coercion that has no clear reason. These are four messages Najīb al-Kailānī conveyed through the novel which everyone should be aware of if he/she expect happiness and peace. Neglecting these for criteria will lead the contrary, as narrated through the novel novel Lail wa Qudhban, the story ends with bad suffering and divorce, as experienced by Inayah.